2008
DOI: 10.1007/s12010-008-8247-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon and Nitrogen Sources and Oxygenation on the Production of Inulinase by Kluyveromyces marxianus

Abstract: Cultivations of Kluyveromyces marxianus var. bulgaricus ATCC 16045 were performed on both minimal and complex media using different carbon and nitrogen sources either in the presence or absence of aeration. The results collected were worked out and compared so as to provide a useful contribution to the optimization of inulinase production. Kinetics of extracellular inulinase release were similar on glucose, fructose, and sucrose. Inulinase was detected at basal level since the beginning of batch runs on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…bulgaricus out of three carbon sources tested, i.e. glucose, fructose, and sucrose, the latter substrate resulted in the highest inulinolytic activity of 15.4 U/mL at 30 g/L and 208 U/mL at 20 g/L . Although it was a different microorganism, these data at least confirmed the present results about the usefulness of sucrose for the production of inulinases.…”
Section: Discussionsupporting
confidence: 88%
“…bulgaricus out of three carbon sources tested, i.e. glucose, fructose, and sucrose, the latter substrate resulted in the highest inulinolytic activity of 15.4 U/mL at 30 g/L and 208 U/mL at 20 g/L . Although it was a different microorganism, these data at least confirmed the present results about the usefulness of sucrose for the production of inulinases.…”
Section: Discussionsupporting
confidence: 88%
“…With NH 4 OH or urea (Equations 4 and 5), the balances predict a slight alkalinization since OH − ions are formed. The consumption of some KOH with urea as an N source is contradictory to this finding, but it should be kept in mind that the final pH was higher than the initial pH ( Figure 3B); synthesis of organic acids (acetate, pyruvate, 2-oxoglutarate, and succinate were by-products of aerobic sugar metabolism of K. marxianus [16,68,70,71]) presumably caused KOH consumption, and consumption of these acidic metabolites after depletion of sugar alkalinized the medium. But such temporary metabolite accumulation was not considered at balancing.…”
Section: Stoichiometry Of Yeast Growthmentioning
confidence: 81%
“…For example, it was reported that K. marxianus DSM 5420 produced 10 g ethanol L −1 from 120 g lactose L −1 under strict aerobic conditions . A shift to ethanol production could be a consequence of an imbalance between glycolysis and the respiratory chain, or to an oxygen, thiamine or iron limitation . A respiro‐fermentative metabolism was observed in a continuous culture of a K. lactis strain when the dilution rate was increased to above 0.4 h −1 ; in this case ethanol production was attributed to a nicotinamide limitation .…”
Section: Discussionmentioning
confidence: 99%